Early Onset Benign Occipital Epilepsy (Panayiotopoulos syndrome): a case Report & Literature Review (Journal of National Institute of Neurosciences Bangladesh, 2015)
Panayiotopoulos syndrome is a type of benign childhood epilepsy syndrome characterized by episodic autonomic and mainly emetic symptoms. It predominantly affects children of 3-6 years of age (13% of those with one or more non-febrile seizures). EEG shows great variability, with occipital, extra-occipital spikes or brief generalised discharges alone or in combination; it may also be consistently normal. Despite the high prevalence of autonomic status epilepticus, the prognosis of Panayiotopoulos syndrome is usually excellent and most do not require anti epileptic medications. Remission usually occurs within 1-2 years from onset. One third have a single seizure but 5-10% may have more than 10 seizures or a more prolonged course. We present a 5 year old boy with this condition, who presented with episodes of severe vomiting, deviation of eyes, focal seizure, altered sensorium, characteristic EEG in the form of multiple occipital spikes and normal neuroimaging studies.J. Natl Inst. Neurosci Bangladesh 2015;1(1):27-30